Victimization of people by natural disasters: Spatial and temporal distribution of consequences - Mijalković Saša; Cvetković Vladimir M. (Temida, 2014)
This paper is a descriptive statistical analysis of geospatial and temporal distributions of victimized people (killed, injured, affected and damage) with specific reference to geophysical, meteorological, climatological, biological and hydrological disasters that have occurred in the world of from 1900 to 2013 year. In addition, people affected by the various natural disasters could be classified as invisible victims as they are not recognized as victims either by the state or society, and consequently they do not receive adequate protection, assistance and support. Statistical research was conducted on data from the international database of the Centre for Research on Disaster Epidemiology Disaster (CRED) in Brussels. Temporal analysis examined the distribution and effects of natural disasters on people, at intervals of ten years. The same methodology was adopted for analyses of geospatial distribution of victimized people because of natural disasters by continent. The aim of the research is to determine the geospatial and temporal distribution of victimization of people with natural disasters in the world geospace in the period from 1900 to 2013. The survey results clearly indicate an increase in the number and severity of the consequences of natural disasters. [Projekat Ministarstva nauke Republike Srbije, br. 179044: Razvoj metodologije evidentiranja kriminaliteta kao osnova kreiranja efikasnih mera za njegovo suzbijanje i prevenciju]